2008
DOI: 10.1139/x08-084
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen attack and spatial patterns of juvenile mortality and growth in a temperate tree, Prunus grayana

Abstract: To examine whether the Janzen–Connell hypothesis is valid in temperate forests, we investigated the density, growth, mortality, and agents of mortality of seedlings and the density, size, and age of saplings of Prunus grayana Maxim. at three distances (0–3, 6–10, and 16–26 m) from conspecific adults in a temperate forest in Japan. An inoculation experiment was also conducted to test the host range of a leaf pathogen. The probability of mortality was highest at 0–3 m during the first 2 years of growth. Mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 37 publications
3
47
1
Order By: Relevance
“…Wang et al (2010) suggested that species aggregation generally decreased with increasing size class. Unlike some previous studies (He et al 1997;Condit et al 2000;Seiwa et al 2008), we found that mature trees to be more aggregated at small scale than juveniles and premature, perhaps because adult recruitment rates were low and dispersal was poor even in the absence of any environmental heterogeneity (Murrell 2009). In addition, pathogens or herbivores may also play an important role as spacing mechanisms in reducing aggregation in temperate forests (e.g.…”
Section: Spatial Patternscontrasting
confidence: 99%
See 1 more Smart Citation
“…Wang et al (2010) suggested that species aggregation generally decreased with increasing size class. Unlike some previous studies (He et al 1997;Condit et al 2000;Seiwa et al 2008), we found that mature trees to be more aggregated at small scale than juveniles and premature, perhaps because adult recruitment rates were low and dispersal was poor even in the absence of any environmental heterogeneity (Murrell 2009). In addition, pathogens or herbivores may also play an important role as spacing mechanisms in reducing aggregation in temperate forests (e.g.…”
Section: Spatial Patternscontrasting
confidence: 99%
“…In addition, pathogens or herbivores may also play an important role as spacing mechanisms in reducing aggregation in temperate forests (e.g. Seiwa et al 2008). In contrast, we found that overmature trees were randomly distributed at almost all scales and this may be largely due to stochastic mortality or strong intra-and/or interspecific competition for resources (light, water, nutrients, etc.).…”
Section: Spatial Patternsmentioning
confidence: 60%
“…At large scales (>2 m), cluster patterns were present in the 5-10-year, 30-40-year, and >40-year stages, and random distributions occurred in the 10-20-year and 20-30-year stages. It has been shown that some species can be aggregated in small diameter classes, while others become aggregated in large diameter classes [50][51][52]. Our results supported the conclusions of Stoll and Bergius [15], i.e., that the spatial distribution of conspecifics under tree-size asymmetrical (rather than symmetrical) competition can shift from initially clustered, via random, to regular, as a result of density-dependent mortality.…”
Section: Changes In Spatial Patterns In the H Ammodendron Plantationsupporting
confidence: 89%
“…Like some previous studies [7,30], we found that relative smaller size classes plants of H. ammodendron was more aggregated at small scale than bigger ones in the plot, perhaps because H. ammodendron (S) recruitment rates were high and dispersal was rich under condition of environmental heterogeneity. However, the observation that aggregation intensity was weaker in classes with larger size classes even random distribution of H. ammodendron (O) may be due to stochastic mortality or strong intra-and/or interspecific competition for resources (water, nutrients, etc.).…”
Section: Spatial Patternssupporting
confidence: 85%